Afatinib alone or afatinib plus vinorelbine versus investigator's choice of treatment for HER2-positive breast cancer with progressive brain metastases after trastuzumab, lapatinib, or both (LUX-Breast 3): a randomised, open-label, multicentre, phase 2 trial. Issue 16 (December 2015) - Cortés, Javier; Dieras, Véronique; Ro, Jungsil; Barriere, Jérôme; Bachelot, Thomas; Hurvitz, Sara; Le Rhun, Emilie; Espié, Marc; Kim, Sung-Bae; Schneeweiss, Andreas; Sohn, Joo Hyuk; Nabholtz, Jean-Marc; et al.
Summary: Background: Patients with advanced HER2-positive breast cancer frequently develop CNS metastases. The metastases that progress after brain radiotherapy and HER2-targeted systemic therapy are a difficult therapeutic challenge. We aimed to assess the efficacy and safety of afatinib, an irreversible blocker of the ErbB protein family, alone or combined with vinorelbine, compared with treatment of the investigator's choice in women with HER2-positive breast cancer with progressive brain metastases during or after treatment with trastuzumab, lapatinib, or both. Methods: We did this randomised, open-label, multicentre, phase 2 trial in 40 hospitals in Canada, Finland, France, Germany, Italy, Spain, South Korea, and the USA. Women older than 18 years with histologically confirmed HER2-overexpressing breast cancer and CNS recurrence or progression as determined by Response Evaluation Criteria in Solid Tumors (RECIST version 1.1) during or after treatment with trastuzumab, lapatinib, or both, were eligible. We randomly assigned patients (1:1:1) centrally to afatinib 40 mg orally once per day, afatinib 40 mg per day plus intravenous vinorelbine 25 mg/m 2 once per week, or investigator's choice of treatment in cycles of 3 weeks until disease progression, patient withdrawal, or unacceptable toxicity. Treatment assignment was not masked for clinicians or patients, but the trial team was masked until database lock to reduce bias. The primary endpoint, assessed in the intention-to-treat population, was patient benefit at 12 weeks, defined by an absence of CNS or extra-CNS disease progression, no tumour-related worsening of neurological signs or symptoms, and no increase in corticosteroid dose. Safety was assessed in all patients who received at least one dose of a study drug. This completed trial is registered withClinicalTrials.gov, numberNCT01441596 . Findings: Between Dec 22, 2011, and Feb 12, 2013, we screened 132 patients, of whom 121 were eligible and randomly assigned to treatment: 40 to afatinib alone, 38 to afatinib plus vinorelbine, and 43 to investigator's choice. All patients discontinued study treatment before the data collection cutoff on Oct 16, 2014. Patient benefit was achieved in 12 (30·0%; 95% CI 16·6–46·5) patients given afatinib alone (difference vs investigator's choice: −11·9% [95% CI −32·9 to 9·7], p=0·37), 13 (34·2%; 19·6–51·4) given afatinib plus vinorelbine (difference vs investigator's choice: −7·6% [–28·9 to 14·2], p=0·63), and 18 (41·9%; 27·0–57·9) given investigator's choice. The most common treatment-related grade 3 or 4 adverse events were diarrhoea (seven [18%] of 40 patients in the afatinib only group vs nine [24%] of 37 patients in the afatinib plus vinorelbine group vs two [5%] of 42 patients in the investigator's choice group) and neutropenia (none vs 14 [38%] vs four [10%]). Interpretation: Patient benefit with afatinib-containing treatments was not different from that in patients given investigator's choice of treatments; however, adverse events were frequent and afatinib-containing treatments seemed to be less well tolerated. No further development of afatinib for HER2-positive breast cancer is currently planned. Funding: Boehringer Ingelheim.